Latitudinal variation in the potential activity of Atlantic Ocean bacterioplankton revealed through 16S rRNA and 16S rRNA gene metabarcoding - Allen, Ro; Bird, Kimberley E.; Murrell, J. Colin; Cunliffe, Michael (Frontiers in Marine Science, 2023)
The activities of bacterioplankton sustain open ocean biogeochemical and ecological processes, however, little is known about the activity of specific bacterioplankton, especially related to their biogeography across oceanic scales. The Atlantic is the second largest of the world’s oceans and has an essential role in the global carbon cycle. Here, we show congruence in the structure of 16S rRNA and 16S rRNA gene derived bacterioplankton communities throughout the Atlantic Ocean from temperate to tropical regions. We used 16S rRNA:16S rRNA gene ratios as a phylogenetically resolved proxy for potential activity, demonstrating ocean-scale patterns of putative oligotrophy and copiotrophy in major bacterioplankton groups, with spatial niche partitioning being evident at single-nucleotide resolution within some groups, including the Flavobacteria and SAR86. This study examines the potential structure of the active microbiome of the Atlantic Ocean, providing novel insights into the ecology and life history strategies of both well-known and currently understudied bacterioplankton taxa.